Model test on bearing capacity of cemented slurry reinforced pile composite foundation - Xia Bian; Weiheng Peng; Chengchun Qiu; Guizhong Xu; Yikang Yao (Case Studies in Construction Materials, 2023)
This study introduces the Geosynthetic Encased Prestressed (GEP) cemented slurry pile technology to address the challenges posed by waste slurry and dredged soil during infrastructure, urbanization, and underground space development. Laboratory model tests were conducted to assess the influence of prestress and geogrid on the bearing capacity of cemented slurry reinforced piles composited foundation. Results indicate that compared to non-geogrid pile composite foundations, both prestressed and non-geogrid pile composite foundations exhibited enhanced load-bearing capabilities in later stages, with an approximate increase of 25.89%. Additionally, the presence of geogrid effectively reduced settlement in the composite foundation under varying loads. The application of geogrid casings to seal cemented slurry reinforced piles facilitated load transfer downwards, restrained lateral expansion deformation, mitigated pile cracking, and bolstered bearing capacity. Consequently, a bearing capacity calculation equation for the composite foundation of cemented slurry reinforced piles was developed in this study. Parameter analysis demonstrated that higher geogrid tensile strength, smaller aspect ratio, greater cohesion, and internal friction angle of pile filler contributed to increased bearing capacity of cemented slurry reinforced piles. In summary, this study evaluates the viability of GEP cemented slurry piles and the impact of relevant parameters on pile bearing capacity of composite foundation. The findings offer valuable insights for practical engineering applications, advancement of eco-friendly transportation, and fostering sustainable development.